The emergency medical teams initiative in the WHO African region: a review of the development and progress over the past 7 years - Balde, Thierno; Oyugi, Boniface; Mbasha, Jerry-Jonas; Kamara, Rashidatu; Martinez-Monterrey, Lazaro Gilberto; Relan, Pryanka; Lajolo, Camila; Bompangue, Didier; Fortin, Ann; Okeibunor, Joseph; Salio, Flavio; Braka, Fiona; et al. (Frontiers in Public Health, 2024)
Background The WHO Emergency Medical Teams (EMT) Initiative coordinates the deployment of qualified medical teams who promptly respond to public health emergencies (PHEs) and provide quality service during emergencies whilst strengthening capacity. Globally, 40 EMTs have been classified between 2016 and the present (as of the writing of this article in December 2023) and are from across all the WHO regions except the WHO Africa Region (AFRO). However, WHO Africa has prioritised the implementation of EMTs in 10 priority countries to address the public health emergencies (PHEs) affecting the region. Objective This article describes the development and progress of national EMTs in the WHO African Region over the past 7 years and elucidates the main lessons learned and the complexity and challenges in the process. Methods This study employed a case study approach because of its appropriateness in examining a complex social phenomenon in a socio-political context in depth, using multiple lenses simultaneously. Data and information were obtained through document reviews and key informant interviews (KIIs) (n = 5) with the members of the EMT Initiative on shared field experiences. Data were systematically analysed using the Stages of Implementation Completion (SIC) framework, and the lessons learnt were presented using components of a framework from Adini et al. Results The Initiative commenced in the WHO African Region following its launch in December 2017 in Senegal. The assessments of the concept’s engagement (involved learning and deciding), feasibility (reviewing expectation and capacity), and readiness planning (collaborating and preparing) showed that the context-specific (African context) challenges, lessons from different emergency response actions mainly guided the Initiative’s pre-implementation phase in the region and prompted the WHO emergency leadership on the urgency and need for the EMT concept in the region. The assessment of the implementation processes showed progress in key areas, with staff demonstrating improved competency, EMT services maintaining high fidelity, effective consultation launching critical components, and ongoing services providing successful support and monitoring. Creating the N-EMTs and revitalising the EMT concept required an aligned strategy with other regional emergency programmes and a futuristic vision. Proposed sustainability and governance components include creating N-EMT, developing a coordination structure, collaborating with partners, and finalising the N-EMT. Conclusion The Initiative is an imperative component that would allow better-targeted management of health emergencies in the region. The continuous refinement of the EMT initiative is crucial. There is a need to work on additional components, such as a context-specific framework for collaborations and partnerships that would enhance deployment and procurement modalities and the complementarity between other regional initiatives to improve the work. Emphasis should be placed on strengthening local health systems, enhancing training and capacity-building programmes, and fostering regional and international collaborations. Additionally, sustainable funding and resource allocation are essential to ensure the resilience of EMTs in the African region and their long-term success.